Breaking Barriers: A Comprehensive Study on Financial Literacy Impacting Women Entrepreneurs' Financial Behavior - Angelica Y Dangcil; Mary Alexia A Ruiz; Mary Rose R Mateo; Jessica A Alejo (Research Synergy Foundation, 2024)
Several studies have shown that financial literacy is crucial in the business world. Those who are more financially literate tend to manage debt and investment better. Hence, financial literacy is paramount for entrepreneurs, particularly women entrepreneurs, to assist them in their daily transactions. The study explores the link between financial literacy and financial behaviour among women entrepreneurs in Ilocos Norte, Philippines. The study employed a quantitative research design and analyzed survey data collected from 377 women entrepreneurs using structural equation modelling to explore the relationship between financial literacy and financial behaviour. The data collected revealed that women entrepreneurs have sufficient financial literacy. Furthermore, the findings showed that financial behaviour is positively influenced by financial literacy, as demonstrated by linear regression analysis.